Advanced defluoridation from industrial wastewater with high‐concentration fluoride through a novel three‐stage treatment process. (7th April 2021) - Xu, Dechao; Yu, Boping; Lu, Xingxing; Luo, Sushuang; Wang, Weimian; Zeng, Yonghui; Jin, Xingliang; Dai, Zhiguang
Abstract: A novel three‐stage treatment process corresponding to three reactors (R1, R2 and R3) was developed for advanced defluoridation from industrial wastewater with fluoride concentration as high as 245 mg/L. In the first stage (R1), 90.6 ± 0.8% of fluoride was removed through CaF2 precipitation. Subsequently, the second stage (R2) was operated for advanced defluoridation through fluorapatite (FAP) precipitation. Importantly, the residual calcium in effluent of R1 participated in FAP precipitation in R2, reducing extra calcium dosage. In the third stage (R3), further defluoridation was observed in R3, and the final fluoride content in the effluent was as low as 0.15 mg/L in Phase 2. Advanced defluoridation from industrial wastewater with high‐concentration fluoride could be obtained through this process without coagulant addition to reduce sludge production and obtain relative pure chemical precipitates, and residual reagents could be utilized again in the next step during the process to decrease reagents dosage.